Decorrelating detector for asynchronous CDMA channels with adaptive path selection - Ulusoy, AH; Amca, H; Hacioglu, K; Rizaner, A (Iee-Inst Elec Eng, 2002)
The conventional multipath-decorrelating receiver performance depends on the number of resolvable paths. The conventional multipath-decorrelating receiver uses as many branches as the number of resolvable paths of the channel to improve the performance of the system. However, using all of the resolvable paths of the channel in the receiver increases the system complexity and the decorrelating filter implemented by the use of all the resolvable paths produces high noise enhancement. The authors propose a scheme that adaptively selects a subset of the paths reducing both system complexity and noise enhancement. Analytical results that show the tradeoff between noise enhancement and multipath-induced multiple-access interference for better performance are provided.
Keywords: Multiuser Detection; Systems